Clinical features of pregnancy in multidrug-resistant tuberculosis and type I diabetes mellitus comorbidities (a case report). - Raznatovska, O. M.; Fedorec, A. V.; Shalmina, M. O.; Grekova, T. A. (Medicni Perspektivi, 2019)
Objective – to update the literature data with the clinical features of pregnancy in multidrug-resistant tuberculosis (MRD-TB) and type 1 diabetes mellitus (T1DM) comorbidities based on an example from own clinical experience. A clinical case of pregnancy course in MRD-TB and T1DM comorbidities was described based on our own clinical experience. We report the clinical case of newly diagnosed MRD-TB in a 38-year-old woman suffering from T1DM. Her general condition was unstable from satisfactory to moderately severe despite an adequate treatment of MRD-TB and T1DM with manifestations of intoxication syndrome and nephropathy. Adenomyosis with periodic bloody vaginal discharge was diagnosed. There was no clinical-radiological dynamics and sputum culture conversion. After an intensive phase of antimycobacterial therapy within 3 months, the patient got pregnant. Based on the medical indications (MRD-TB, absence of sputum culture conversion and clinical-radiological dynamics, moderate severity of T1DM, nephropathy) and adenomyosis with bloody vaginal discharge, the patient was requested to induce the pregnancy termination, and she consented. On month 7 of antimycobacterial therapy, an extensive drug-resistance of Mycobacterium tuberculosis to antimycobacterial agents and negative dynamics by follow-up chest X-ray were diagnosed. The feature of pregnancy course in MRD-TB and T1DM comorbidities was an unfavorable coexistence of both these diseases simultaneously resulting in an induced abortion. In this case, doctors to working with patients suffering from both MRD-TB and T1DM are recommended to advise patients the use of contraception in order to prevent pregnancy during treatment of active MRD-TB.